La adquisición de competencias en la concepción de aprendizaje del posgrado - Campos-Sánchez, Antonio; Rodríguez, Ismael Ángel; Solari, Natalia; Garzón-Bello, Ingrid Johanna; Sánchez Quevedo, María del Carmen; Bregains, Liliana Elena; Campos, Fernando; Rodríguez, M. A.; Alaminos Mingorance, Miguel (Sociedad Argentina de Investigación Odontológica, 2022)
Fil: Campos Muñoz, Antonio, Universidad de Granada; España.